Budaya Organisasi Dan Stress Kerja: Pengaruh Terhadap Kinerja Karyawan PT. Herfinta Farm And Plantation - Henny Pratiwi; Syah Abadi Mendrofa; Yamolala Zega; Ahmad Prayudi; Fahmi Sulaiman (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
The problem to be studied is that the performance is less than optimal because there are still employees who are not optimal in carrying out their duties as indicated by (a) Implementation of organizational culture that has not been optimally carried out. (b) Delayed completion of pre-determined work because there are several employees who leave the workplace without prior permission and are often seen unemployed and talking about unimportant things during working hours. (c) High absenteeism due to sick and unreasonable employees. This research was conducted in August – October 2019. It was carried out at the Head office of PT. Herfinta Farm and Plantation, Jalan Kapt. Maulana Lubis No. 9 Medan City. The sample in this study were all employees at PT. Herfinta Farm and Plantation which amounted to 30 people. From the results of data processing, it was found that the significance value was 0.0 which was smaller than 0.05 and based on the calculated F value was 24.396 which was greater than the F table of 3.35. From the two analyzes, Ho is rejected, meaning that there are simultaneously independent variables affecting the dependent variable. To improve employee performance, the application of organizational culture and work stress must also be increased at PT. Herfinta Farm and Plantation. Adjusted R Square value is 0.617 or 61.7%. This condition explains that 61.7% of organizational culture variables and work stress have a significant effect on employee performance. This means that from several factors supporting employee performance, organizational culture and work stress factors that affect employee performance the most are 61.7%.